Influência da inativação fotodinâmica sobre a viabilidade e dinâmica de crescimento de Candida albicans - Trescher, Tarquin Freitas (2014)
Fungus Candida albicans is responsible for most of the nosocomial infections which affect immunocompromised individuals. It is highly invasive and capable of destroying or modifying constituents of host cell membrane inducing dysfunction or physical annihilation. Although most isolates of Candida albicans are susceptible to antifungal drugs, uncontrolled use of drugs has promoted the development of resistance and tolerance to fungal pathogens with current antifungals. The clinical implication of the appearance of resistant strains is the search for safer and more effective drugs and also alternative therapies, such a photodynamic, which aims to eliminate the pathogen by the combination of light + photosensitizer. In this work we have investigate the combination of eosin photosensitizer and laser light (532 nm) in order to photodynamic inactivation of Candida albicans. The dye eosin is commonly used in cosmetics or pharmaceuticals and was the first photosensitizer to be used in studies of the inactivation of microorganisms. The wavelength of 532 nm used for laser irradiation is suitable for photoinactivation because eosin has a maximum absorbance at 512 nm. The results indicated susceptibility of the fungi to fluency values higher than 150 J/cm2 or high pre-irradiation time. Fluorescence and atomic force microscopy corroborate the inactivation results and indicate that and cell death must occur due to damage to the cell wall. Colony growth is also influenced by the combination of light + photosensitizer and can be described by means of growth models of fractal interfaces. It was concluded that the proliferation of the fungi should be inhibited in the center of the colonies and the analysis of the edges give an indication about the dynamics of growth and cell reproduction. These results can be a starting point in the search for new clinical strategies.